Simultaneous effect of the transcranial direct current stimulation ‎and observational learning on learning of basketball free throw - Roya Mahdipour; Mahdi Namazizadeh; Rokhsareh Badami; Hamid Mirhosseini (University of Tehran, 2022)
Introduction: The purpose of the current study was to examine the simultaneous effect of the ‌transcranial direct current stimulation (tDSC) and observational learning on learning ‌of basketball free throw. ‌Methods: In semi-experimental study with repeated measure design, 30 novice female ‌students in free basketball throw accessibly selected and randomly located in 2 ‌tDCS with model observation and artificial stimulation with model observation ‌groups. In pre test phase, participants throw 15 trials basketball free throw. ‌Intervention phase done in 5 consecutive days that each day electrical stimulation ‌of the brain was performed from the motor cortex (C3 anode & Fp2 anode), and ‌artificial stimulation with model observation, and then participants performed 15 ‌free basketball throws. In last session post test phase executed. One week and 21 ‌days after post test phase respectively executed short term and long term retention ‌phase. Data analyzed with ANOVA with repeated measure statistical method.‌Results: The result indicated that tDCS with model observation (F= 22.327, sig =0.0001, η2 =0,615) and artificial stimulation with model observation (F= 3.044, sig =0.023, η2 =0,179) significantly improved basketball free throw. Other results indicated that ‌tDCS with model observation than artificial stimulation with model observation ‌cause improvement basketball free throw in post test (p=0.002), short term test (p=0.002) and long term test (p=0.001). ‌Conclusion: Overall, the results of the current study indicated that tDCS with model observation ‌can be effective as a new training method in addition to model observation to ‌improve basketball free throw skills‌.